2015
DOI: 10.1002/lary.25211
|View full text |Cite
|
Sign up to set email alerts
|

A ten‐year review of soft tissue reactions around percutaneous titanium implants for auricular prosthesis

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…In our population, we did not observe a statistically significant difference in adverse skin reactions between age groups. This finding is in contrast to the study by Dun et al (9) and Tzortzis et al (10), that children are more prone to adverse skin reactions when compared to adults and the elderly. A similar study on adults by Husseman et al (11) reported an adverse skin reaction rate of 14.7%.…”
Section: Discussioncontrasting
confidence: 99%
“…In our population, we did not observe a statistically significant difference in adverse skin reactions between age groups. This finding is in contrast to the study by Dun et al (9) and Tzortzis et al (10), that children are more prone to adverse skin reactions when compared to adults and the elderly. A similar study on adults by Husseman et al (11) reported an adverse skin reaction rate of 14.7%.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there are skin complications related to percutaneous devices, and some patients who cannot or do not want to use percutaneous devices for dermatologic or esthetic reasons may have the option of an active middle ear prosthesis [1] . Bone conduction implant surgery can also result in complications related to osteointegration, and rarely, major complications are associated with drilling a small hole toward the dura [2] .…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable outcome is the fact that revision surgery was not needed in our patients whereas in the literature, also in bone-anchored hearing, the reported necessity for revision surgery varies considerably, even up to approximately one-third of the patients [28, 31, 32, 34]. This might be associated with different surgical techniques (tissue preservation vs. tissue reduction [2224]).…”
Section: Discussionmentioning
confidence: 82%
“…Jacobsson et al reports adverse tissue reactions in 9.68% of the observations in a paediatric population [31]. Tzortzis et al reports a higher incidence of adverse soft-tissue reactions in children compared to adults (Holgers grade 2 or higher, 28 vs. 3% of the patients) [32]. …”
Section: Discussionmentioning
confidence: 99%